An effect of temperature on structural, optical, photoluminescence and electrical properties of copper oxide thin films deposited by nebulizer spray pyrolysis technique. (February 2018) - Prabu, R. David; Valanarasu, S.; Ganesh, V.; Shkir, Mohd; AlFaify, S.; Kathalingam, A.; Srikumar, S.R.; Chandramohan, R.
Abstract: In this work, copper oxide thin films were deposited on glass substrate by nebulizer spray pyrolysis technique with different temperatures (i.e. 250–320 °C). All the deposited films were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), Laser Raman, UV–Vis, Photoluminescence and Hall Effect measurements for the Structural, morphological, vibrational, optical and electrical properties. The XRD studies confirmed that the films deposited with different temperatures from 250 to 300 °C possess single cubic crystal structure phase of cuprous oxide (Cu2 O) whereas the films deposited at 310 and 320 °C were found to have a mixed phase of CuO and Cu2 O. When the temperature reaches above 310 °C the Cu2 O phase become unstable and started to convert as CuO. Laser Raman studies confirmed that the observed peaks at 109, 148, 219, 416, 515 and 635 cm −1 are belong to Cu2 O phase deposited at 250 and 280 °C. However, the films deposited at 310 °C and 320 °C having additional peaks at 273, 327 and 619 cm −1 which conforms the presence of mixed (CuO and Cu2 O) phase. The AFM studies shows that the deposited films has uniformly distributed with homogeneity and the particles extended all over the surface. Optical measurement showed that the band gap of deposited thin films in the range of 2.44–1.97 for 250–320 °C, respectively. A single and strong emission peak at 617 nm is observed in PL spectra, which conforms the copper oxide film. Hall Effect measurements showed that all the films are of p-type conductivity with resistivity (ρ) of 4.61 × 10 2 Ω cm, carrier concentration (n) of 13.53 × 10 15 cm −3 and mobility of 1.0 cm 2 /vs at 320 °C temperature. The low activation energy of 0.012 eV were observed for the film deposited at 320 °C.